Gênero e biopoder: a “invenção” da violência contra a mulher no discurso policial e nas práticas das delegacias da mulher de Teresina - PI - Villa, Eugênia Nogueira do Rêgo Monteiro (Universidade do Vale do Rio dos Sinos, 2014)
The research aims to determine to what extent the actions taken by the WPS Teresina actualize the rights of women in situations of violence. For this purpose shall be used the dialectical method, promoting a dialogue between the theoretical bases that surround the idea of gender, violence against women and biopolitics and the dynamics of relationships that are established in those precincts under the focus of the police and the speech speaks of women attending there. Starts the route in consistent theoretical and normative field studies into the categories of gender gende based violence and biopower. The gender and gender violence categories have language as a privileged field for the study. Already the idea of biopower assist in understanding the meaning of the WPS as biopolitics strategy invented by the state to deal with violence against women. Imbricate gender violence and biopolitics the reason of the existence of specialized police will be understood. So that in a second moment an immersion shall be made in police woman Teresina to delimit the field of effectiveness from the perspective of the dynamics of relationships there are established between policemen and women attended. Thus will be analyzed the profile of police server and expressed his speech in the records of the events and the profile of the woman answered, his vision for the precinct on other biopolitical strategies and legal standards aimed to protect women in situations of violence as well as his account of the violence suffered. Once outlined the material field resumes the discussion from the dialogue between the discourses of the police and the categories of women studied from the theoretical bases.
Keywords: Gênero; Violência contra a mulher; Biopolítica; Linguagem; Gender; Violence against women; Biopolitics; Language; ACCNPQ::Ciências Sociais Aplicadas::Direito